COMPARATIVE STUDY OF DIFFERENT PROGRAMMING LEARNING TOOLS ON STUDENTS' MOTIVATIONAL AND ATTAINMENT LEVEL - OSMAN, MOHAMAD AMIN (2013)
The development of Information and Communication Technology (ICT) has greatly influenced the way people live and work. The innovation in the field of ICT is also expected to propel the country towards the realization of Vision 2020. Application ofICT in learning is also gaining attention and popularity through implementation of various programs such as the introduction of Computer in Education program in schools which was later extended to the ICT Literacy (ICTL) program.